Microglia increase tight-junction permeability in coordination with Müller cells under hypoxic condition in an in vitro model of inner blood-retinal barrier. (April 2021) - Inada, Makoto; Xu, Heping; Takeuchi, Masaru; Ito, Masataka; Chen, Mei
Abstract: Microglia and Müller cells (MCs) are believed to be critically involved in hypoxia-induced blood-retinal barrier (BRB) disruption, which is a major pathogenic factor of various retinopathies. However, the underlying mechanism remains poorly defined. The inner BRB (iBRB) is primarily formed of microvascular endothelial cells (ECs) with tight junction (TJ), which are surrounded and supported by retinal glial cells. We developed a novel in vitro iBRB model sheet by sandwiching Transwell membrane with layered mouse brain microvascular ECs (bEnd.3) and mouse retinal MCs (QMMuC-1) on each side of the membrane. Using this model, we tested the hypothesis that under hypoxic condition, activated microglia produce inflammatory cytokines such as interleukin (IL)-1β, which may promote vascular endothelial growth factor (VEGF) production from MCs, leading to TJ disruption. The iBRB model cell sheets were exposed to 1% oxygen for 6 h with or without mouse brain microglia (BV2) or IL-1β. TJ structure and function were examined by zonula occludens (ZO)-1 immunostaining and fluorescein isothiocyanate permeability assay, respectively. Relative gene expression of IL-1β in BV2 under normoxic and hypoxic conditions was examined by real-time reverse transcription-polymerase chain reaction. VEGF protein concentration in QMMuC-1 supernatants was measured by enzyme-linked immunosorbent assay. The bEnd.3 cell sheet incubated with BV2 in hypoxic condition or with IL-1β in normoxic condition showed abnormal localization of ZO-1 and aberrated barrier function. Under normoxic condition, EC-MC iBRB model cell sheet showed lower permeability than bEnd.3 cell sheet. Under hypoxic conditions, the barrier function of EC-MC iBRB model cell sheet was more deteriorated compared to bEnd.3 cell sheet. Under hypoxic condition, incubation of EC-MC iBRB model cell sheet with BV2 cells or IL-1β significantly increased barrier permeability, and hypoxia-treated BV2 cells expressed significantly higher levels of IL-1β mRNA. Incubation of QMMuC-1 with IL-1β increased VEGF production. These results suggest that under hypoxic condition, microglia are activated to release proinflammatory cytokines such as IL-1β that promote VEGF production from MCs, leading to disruption of iBRB function. Modulating microglia and MCs function may be a novel approach to treat hypoxia-induced retinal BRB dysfunction. Highlights: Barrier function of endothelial cells is enhanced by co-culturing with Müller cells. Endothelial-Müller cell co-culture is a unique model of the inner blood retinal barrier (iBRB). Microglia do not affect iBRB integrity in normal culture condition but impair the barrier under hypoxic condition. Microglia release excessive amount of IL-1β under hypoxic condition. IL-1β induces Müller cell VEGF production and damages the iBRB.